UPAYA MENINGKATKAN KEMAMPUAN BERBICARA MELALUI PERMAINAN WAYANG KERTAS PADA ANAK USIA 5-6 TAHUN DI PAUD HARAPAN KELURAHAN SUKAMULIA KECAMATAN SAIL KOTAMADYA PEKANBARU - Wahyuningsih Wahyuningsih; Zulkifli N Zulkifli N; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study aims to determine how much Effect Paper Puppet Play in children aged 5-6 years against Speech Child. This study consists of two variables: Puppet Play Paper and Speech. The hypothesis proposed in this study are as follows: Games of paper puppets can enhance the ability to speak in children aged 5-6 years in early childhood Hope, Village Sukamulia, District municipality Sail, Pekanbaru. The study involved 20 sabjek ie 506 year olds in early childhood Sukamulia Village, District municipality Sail, Pekanbaru. Methods of data collection in this study using observation. Data collection techniques in this research use descriptive qualitative data.The results showed no significant positive relationship between the game Puppet Paper with Speech in children aged 5-6 years in early childhood in Hope, Village Sukamulia, District municipality Sail, Pekanbaru. From the above data analysis is known to occur upgrades speaking children aged 5-6 years through a paper puppet game. The average rate earned on pre-cycle activity reached 33.75% in the category yet Evolving (BB), then the first cycle average rate reached 40.68% are in category Start Evolving (MB) and the second cycle the average rate of return increased to 63.18%.Keywords: Paper Puppet Games, Speech.